Manganese and copper levels in patients with primary biliary cirrhosis and primary sclerosing cholangitis - Dastych, Milan; Husová, Libuše; Aiglová, Květoslava; Fejfar, Tomáš; Dastych, Milan (Scandinavian journal of clinical & laboratory investigation, 2021)
The liver and the biliary tree form the main excretory route of manganese (Mn) and copper (Cu). Cholestasis, can lead to the accumulation of these trace elements in the organism, resulting in toxicity to the basal ganglia of the central nervous system. The aim of our study was to reveal the influence of long-term cholestasis on the Mn and Cu levels in the blood of patients with primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC). We recruited patients with PBC (n = 20) and PSC (n = 32). A control group (n = 40) was also set up. We also examined serum bile acid concentrations and liver enzyme activities. We did not observe any significant differences in any of these parameters between the PBC and PSC groups. The Mn and Cu levels in the PBC and PSC patients differed significantly from the that in the control group (p < 0.0001 and p < .021, respectively). Patients in whom the laboratory cholestasis markers normalized during ursodeoxycholic acid treatment (18/52;35%) presented with significantly lower levels of Mn and Cu (p = .015 and p = .012, respectively). Ten PSC patients showed normal levels of Mn and Cu six months after liver transplantation. Fine tremors, rigidity, dysarthria, and hypomimia were reported in nine (23%), eight (20%), four (10%), and eight (20%) patients, respectively. In addition to monitoring the cholestasis levels, liver function, and Mn and Cu levels during the long-term treatment of PBC and PSC patients, it is important to also regularly monitor the occurrence and development of extrapyramidal symptoms of Parkinson's-like syndromes.
Keywords: mladý dospělý; Liver Cirrhosis, Biliary; sklerozující cholangitida; Humans; lidé; lidé středního věku; Manganese; transplantace jater; Middle Aged; Case-Control Studies; biliární cirhóza; Female; Male; Adult; měď; mužské pohlaví; Aged; studie případů a kontrol; ženské pohlaví; mangan; Cholangitis, Sclerosing; Young Adult; Liver Transplantation; dospělí; Copper; senioři